ANALYSIS OF THE EFFECT OF FINANCIAL RATIOS ON BID-ASK SPREAD WITH PROFIT CHANGE AS MODERATING VARIABLES IN BANKING COMPANIES IN INDONESIA STOCK EXCHANGE - Mufti, Ichsan (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aims (1) to test and analyse the effect of Financial Ratios namely Cash Ratio (CsR), Loan to Deposit Ratio (LDR), Non-Performing Loans (NPL), Net Profit Margin (NPM), Capital Adequacy Ratio (CAR), Debt to Equity Ratio (DER) and Third Party Funds (DPK) partially against Bid-Ask Spreads at Banking companies on the Indonesia Stock Exchange. (2) Examining and analysing the effect of Financial Ratios (CsR, LDR, NPL, NPM, CAR, DER and DPK) simultaneously on Bid-Ask Spreads on Banking companies on the Indonesia Stock Exchange. (3) Determine whether Changes in Profit can moderate the effect of Financial Ratios (CsR, LDR, NPL, NPM, CAR, DER and DPK) on Bid-Ask Spreads on Banking companies on the Indonesia Stock Exchange. The object of this study is the Banking Companies listed on the Indonesia Stock Exchange from 2014-2017 as many as 44 companies. The sample selection technique is by survey method. The number of companies selected was 38 companies. The data source comes from the official site of the Indonesia Stock Exchange, www.idx.co.id. Data analysis techniques in the study are multiple linear regression analysis and residual test. The results showed that (1) partially CsR, CAR, DER and DPK variables had a negative and significant effect on Bid-Ask Spread while LDR, NPL and NPM variables had no significant effect on Bid-Ask Spread on banking companies on the Indonesia Stock Exchange. (2) Simultaneously financial ratios (CsR, LDR, NPL, NPM, CAR, DER and DPK) have a significant effect on Bid-Ask Spreads of banking companies on the Indonesia Stock Exchange. (3) Changes in Profit cannot moderate the effect of Financial Ratios (CsR, LDR, NPL, NPM, CAR, DER and DPK) on Bid-Ask Spreads on Banking companies on the Indonesia Stock Exchange.